ANALISIS SUMBER AIR BAKU UNTUK MEMENUHI KEBUTUHAN AIR RUSUNAWA GIRIASIH DI KECAMATAN BATUJAJAR KABUPATEN BANDUNG BARAT - Apik Adzani Diandi; Eka Wardhani; Agung Ghani Kramawijaya (Journal of Environmental Engineering and Waste Management, 2019)
Administratively, Giriasih Rusunawa located at Jalan Griya Asri Permai, Kampung Babakan RT 01 and 02 RW 18 Kampung Babakan, Giriasih Village, Batujajar Sub-District, West Bandung Regency, is in a difficult area for clean water. This study aims to determine the alternative sources of raw water that will be used to meet water needs in Rusunawa. Alternative raw water sources, namely groundwater, surface and rain. The method used by comparing water quality with quality standards. The parameters tested consisted of physical, chemical, and microbiological parameters. The quality monitored is compared to the quality standard based on Government Regulation Number 82 of 2001 Class I concerning Management of Water Quality and Water Pollution Control and PerMenKes No. 492 of 2010 concerning Drinking Water Quality Requirements. Based on the results of analysis of raw water sources, surface water is very possible to be used as a source of water to meet the needs of water in flat from all aspects. Quantity aspect, Saguling Reservoir guarantees continuous availability of raw water, which is 4,000 l / sec and can still be developed up to 5,000 l / sec. Parameters that do not meet quality standards on surface water are: BOD, COD, Phosphate and Manganese. Based on the results of the calculation of water requirements of 3 l / sec to serve the water needs in the flat.